Pengaruh Game Online Terhadap Perkembangan Emosi pada Siswa Sekolah Dasar - Widiyah Dwi Wulan Sari; Danar Rizky Rananda; Haikal Bestanun Arifin (Yayasan Citra Dharma Cindekia, 2024)
This research aims to find out how online games influence the emotional and social development of elementary school children. The method in this research uses a qualitative approach. The targets of this research were three elementary school aged children who played online games. The data collection techniques used in this research are observation and interviews. Based on the output of interviews and observations that researchers conducted on five elementary school age children who used online games, researchers found both positive and negative influences. Positive influences include children accessing technological information easily, children knowing various implementations of using online game units, and children getting to know new vocabulary in foreign languages. The negative influences of online games on children's emotional and social development include children getting angry easily, being more aggressive, and lacking communication relationships with the people around them